Preparation of Ibuprofen-loaded Poly-(Methyl Vinyl Ether-co-maleic Anhydride) Nanoparticles by Solution-enhanced Dispersion by Supercritical CO2 (Journal of Fiber Bioengineering and Informatics, 2012)
Ibuprofen-loaded Poly-(methyl vinyl ether-co-maleic anhydride) (PVM/MA) nanoparticles weresuccessfully prepared by Solution-enhanced Dispersion by Supercritical CO_2 (SEDS). Ibuprofen andPVM/MA were first homogeneously dissolved in acetone, and then the resulting solution wassimultaneously sprayed with supercritical CO_2 through a coaxial nozzle, forming ibuprofen-PVM/MAnanoparticles. FTIR spectra demonstrated that ibuprofen was successfully incorporated into PVM/MAand the SEDS process was a typically physical process. The absolute value of the zeta potential of theobtained ibuprofen-PVM/MA nanoparticles was larger than 40 mV, indicating a good stability of thenanoparticles in aqueous suspension and suitability for oral administration. Analysis ofThermogravimetry-differential Scanning Calorimetry (TG-DSC) revealed that the effect of the SEDSprocess on the thermostability of the drug and the coating polymer was negligible. The results of GasChromatography (GC) analysis confirmed that the SEDS process could efficiently remove the organicresidue. The drug dosage of 20% corresponded to a final drug load of 5.3 ± 0.2%, which appeared to berelatively low and indicated that most of the ibuprofen was lost in the supercritical CO_2. Significantdifferences existed among the drug release profiles obtained from different release media; a mediumwith a low pH could efficiently prevent the release of ibuprofen from ibuprofen-PVM/MA nanoparticles,which works to reduce the adverse effects of ibuprofen on the stomach and makes ibuprofen-PVM/MAnanoparticles suitable for oral administration.